2011
DOI: 10.1007/s10384-011-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity assays of new artificial tears containing 2-methacryloyloxyethyl phosphorylcholine polymer for ocular surface cells

Abstract: The MPC eye drops were tolerable to ocular surface cells, and comparable to single doses of clinically approved drugs containing sodium hyaluronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
(40 reference statements)
4
18
1
Order By: Relevance
“…The methods for cell culture, the cytotoxicity assays, and data evaluation have been described in detail elsewhere 2. Briefly, the following commercially available cell lines were used: SIRC (rabbit corneal epithelium; ATCC CCL-60; American Type Culture Collection [ATCC], Manassas, VA); BCE C/D-1b (bovine corneal epithelial cells; JCRB- 9129; Health Science Research Resource Bank, Osaka, Japan); RC-1 (rabbit corneal epithelium; JCRB-0246; Health Science Research Resource Bank); and Chang conjunctiva (human conjunctival cells; ATCC CCL-20.2; ATCC).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods for cell culture, the cytotoxicity assays, and data evaluation have been described in detail elsewhere 2. Briefly, the following commercially available cell lines were used: SIRC (rabbit corneal epithelium; ATCC CCL-60; American Type Culture Collection [ATCC], Manassas, VA); BCE C/D-1b (bovine corneal epithelial cells; JCRB- 9129; Health Science Research Resource Bank, Osaka, Japan); RC-1 (rabbit corneal epithelium; JCRB-0246; Health Science Research Resource Bank); and Chang conjunctiva (human conjunctival cells; ATCC CCL-20.2; ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, patients’ ocular surface cells come in direct contact with eyedrop formulations. Thus, to reflect the actual situation, we have tried to improve cytotoxicity assays for ocular cells 26. In these studies, ocular surface cells came into direct contact with drug formulations in the absence of culture medium.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipidure®, a copolymer of butyl methacrylate and 2-methacryloyloxyethyl phosphorylcholine, was chosen as the coating material; this material has been previously shown to reduce the adherence of fibroblasts on poly(ethylene telephthalate) in comparison with uncoated material [23]. In previous work, Mang et al and Ayaki et al [24, 25] showed using in vitro studies that Lipidure® materials provide good cytocompatibility. To determine the effectiveness of Lipidure®-coated E-shell 300 materials in preventing macrophage adhesion, we examined uncoated materials and coated materials (n=3) at 2 hours, 24 hours, and 48 hours (data not shown) after seeding.…”
mentioning
confidence: 99%